Pola Komunikasi Islam dalam Mengasuh Anak (Studi pada Aktivis Perempuan di Perwakilan Daerah Salimah Samarinda) - Sri Ayu Rayhaniah Ayu (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
This study aims to determine how the application of Islamic communication patterns in parenting by women activists, in this case is the Muslimah Brotherhood Organization (Salimah) Samarinda City. This research is a qualitative descriptive study and the method is field research. Data collection tehniques use observation, interview and documentation. The results of this research are application of Islamic communication patterns namely: (1) The communication pattern in the form of question is always used in daily life, to ask about the children’s condition, opinion or remind them about something. (2) The pattern of communication in the form of dialogue (question and answer) is often used to explore deeper desire, opinion or children’s condition. (3) The pattern of communication in the form of an oath, according to research conducted by researchers, is rarely even almost never carried out by parents to children, considering that oaths are sacred things in the custom of Indonesian. (4) The communication pattern in the form of promise and threat are considered quite effective in caring for children, therefore children are motivated to apply kindness and stay away from prohibition. (5) Communication patterns in the form of proverbs or parables are often used to convey something that is difficult to explain. (6) The communication pattern in the form of a story is very effective in impressing the children’s soul. (7) The communication pattern in the form of repetition (tikrar) to convey important thing must always be repeated to remind the children. (8) The communication pattern in the form of gradual is considered very necessary and effective in caring for children because each child has different age and acceptance.